The Ninth Nugget - Roy, Ron 1940-; Gurney, John (New York : Random House, 2001)
When Dink, Josh, and Ruth Rose visit a dude ranch in Montana, they find themselves with another mystery to solve, this one involving the theft of money from the ranch's safe and of a large gold nugget that Josh had found.
"A stepping stone book."
Keywords: Dude ranches -- Fiction; Robbers and outlaws -- Fiction; Mystery and detective stories